Clinicopathological features, MCPyV status and outcomes of Merkel cell carcinoma in solid‐organ transplant recipients: a retrospective, multicentre cohort study. (14th June 2022) - Ferrándiz‐Pulido, C.; Gómez‐Tomás, A.; Llombart, B.; Mendoza, D.; Marcoval, J.; Piaserico, S.; Baykal, C.; Bouwes‐Bavinck, J.N.; Rácz, E.; Kanitakis, J.; Harwood, C.A.; Cetkovská, P.; et al.
Abstract: Background: The proportion of Merkel cell carcinomas (MCCs) in solid‐organ transplant recipients (SOTR) harbouring Merkel cell polyomavirus (MCPyV) is unknown, as are factors affecting their outcomes. Objective: To describe clinicopathological features of MCC in SOTR, investigate the tumoral MCPyV‐status and identify factors associated with tumour outcomes. Methods: Retrospective, international, cohort‐study. MCPyV‐status was investigated by immunohistochemistry and polymerase chain reaction. Results: A total of 30 SOTR and 44 consecutive immunocompetent patients with MCC were enrolled. SOTR were younger at diagnosis (69 vs . 78 years, P  < 0.001). Thirty‐three percent of SOTR MCCs were MCPyV‐positive vs . 91% of immunocompetent MCCs ( P  = 0.001). Solid‐organ transplantation was associated with an increased cumulative incidence of progression (SHR: 3.35 [1.57–7.14], P  = 0.002), MCC‐specific mortality (SHR: 2.55 [1.07–6.06], P  = 0.034) and overall mortality (HR: 3.26 [1.54–6.9], P  = 0.002). MCPyV‐positivity and switching to an mTOR inhibitor (mTORi) after MCC diagnosis were associated with an increased incidence of progression (SHR: 4.3 [1.5–13], P  = 0.008 and SHR: 3.6 [1.1–12], P  = 0.032 respectively) in SOTR. Limitations: Retrospective design and heterogeneity of SOTR cohort. Conclusions: MCPyV appears to play a less prominent role in the aetiopathogenesis of MCC in SOTR. SOTR have a worse prognosis than their immunocompetent counterparts and switching to an mTORi after the diagnosis of MCC does not improve progression.